Dietary Supplementation of L-Arginine and N-Carbamylglutamate Attenuated the Hepatic Inflammatory Response and Apoptosis in Suckling Lambs with Intrauterine Growth Retardation - Hao Zhang; Yaotian Fan; Mabrouk Elsabagh; Shuang Guo; Mengzhi Wang; Honghua Jiang (Hindawi Limited, 2020)
L-arginine (Arg) is a semiessential amino acid with several physiological functions. N-Carbamylglutamate (NCG) can promote the synthesis of endogenous Arg in mammals. However, the roles of Arg or NCG on hepatic inflammation and apoptosis in suckling lambs suffering from intrauterine growth restriction (IUGR) are still unclear. The current work is aimed at examining the effects of dietary Arg and NCG on inflammatory and hepatocyte apoptosis in IUGR suckling lambs. On day 7 after birth, 48 newborn Hu lambs were selected from a cohort of 432 twin lambs. Normal-birthweight and IUGR Hu lambs were allocated randomly (n=12/group) to control (CON), IUGR, IUGR+1% Arg, or IUGR+0.1% NCG groups. Lambs were fed for 21 days from 7 to 28 days old. Compared with CON lambs, relative protein 53 (P53), apoptosis antigen 1 (Fas), Bcl-2-associated X protein (Bax), caspase-3, cytochrome C, tumor necrosis factor alpha (TNF-α), nuclear factor kappa-B (NF-κB) p65, and NF-κB pp65 protein levels were higher (P<0.05) in liver from IUGR lambs, whereas those in liver from IUGR lambs under Arg or NCG treatment were lower than those in IUGR lambs. These findings indicated that supplementing Arg or NCG reduced the contents of proinflammatory cytokines at the same time when the apoptosis-related pathway was being suppressed, thus suppressing the IUGR-induced apoptosis of hepatic cells.